Anthony Adverse - Korngold, Erich Wolfgang 1897-1957 (Warner Home Video, 2015)
"In 18th-century Italy, an orphan's debt to the man who raised him threatens to separate him forever from the woman he loves." [imdb.com]
Original: USA 1936
Special features: Vintage featurette "The Making of a Great motion picture" ; theatrical trailer
Bildformat 1.37:1
Keywords: Film; DVD-Video